Reduction of Multidrug-Resistant (MDR) Bacterial Infections during the COVID-19 Pandemic: A Retrospective Study - Bentivegna, Enrico (Int J Environ Res Public Health, 2021)
Multidrug-resistant (MDR) organisms are emerging as some of the main healthcare problems worldwide. During the COVID-19 pandemic, several Infection Prevention and Control (IPC) measures have been adopted to reduce nosocomial microorganism transmission. We performed a case–control study to identify if the incidence of MDR bacterial infections while using pandemic-related preventive measures is lower than in previous years. From 2017 to 2020, we monitored hospital discharges over a four-month period (P #) (1 March to 30 June) in St. Andrea Hospital, Rome. In total, we reported 1617 discharges. Pearson’s chi-squared test was used to identify significant differences. A value of p ≤ 0.05 was considered statistically significant. A significant reduction in the incidence of total MDR bacterial infections was observed during the pandemic compared to in prepandemic years (p < 0.05). We also found a significantly higher incidence of MDR bacterial infections in COVID-19 departments compared with other medical departments (29% and 19%, respectively), with extended-spectrum β-lactamase Klebsiella pneumoniae as the pathogens presenting the highest increase. This study demonstrates that maintaining a high level of preventive measures could help tackle an important health problem such as that of the spread of MDR bacteria.